Rare Presentation, Critical Diagnosis: Primary Actinomycosis of the Foot - Alexandra Maria Dorobanțu; Mihai Lupu; Liliana Gabriela Popa; Raluca Tatar; Calin Giurcaneanu; Irina Tudose; Olguta Anca Orzan (MDPI AG, 2024)
Actinomycosis, an uncommon granulomatous infection caused by the Actinomyces species, rarely targets as primary involvement the limb and is often linked to traumatic incidents. In this report, we present the case of a 44-year-old female who developed multiple small nodules on her left foot over approximately 12 months. Some nodules exhibited firmness and a violet hue, while others discharged a yellowish fluid. The patient had no significant comorbidities. Despite thorough blood paraclinical assessments, including complete blood count, serological HIV testing, and QuantiFERON-TB Gold testing, no abnormalities were detected. Bacteriological examinations and cultures of the discharge yielded negative results. Dermatoscopic examination revealed ovoid yellowish structures, with confocal microscopy highlighting granulomas. A subsequent skin biopsy confirmed characteristic changes indicative of actinomycosis. Although systemic antibiotic therapy with penicillin derivatives was initially considered, the patient's documented allergic history to this medication class, verified through allergological testing, prompted the initiation of doxycycline treatment. Notably, significant improvement was observed at the 3-month follow-up. This case underscores the importance of reporting rare instances of actinomycosis due to its diagnostic complexity and management challenges.